2014
DOI: 10.2147/ijn.s69013
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of gold nanoclusters in human liver cancer cells

Abstract: In this study, we synthesized water-soluble fluorescent gold nanoclusters (Au NCs) stabilized with dihydrolipoic acid (DHLA). The cytotoxicity of these Au NCs was then assessed in the normal human hepatic cell line (L02) and the human hepatoma cell line (HepG2) at different exposure times. Cell viability was normal in both cell lines at 24 hours and 48 hours; however, the growth of HepG2 cells was significantly inhibited at 72 hours. The change in lactate dehydrogenase level was strongly correlated with cell v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…This uptake did not translate into significant cytotoxicity after 24 h of exposure. The latter is consistent with 3.2 nm dihydrolipoic-coated gold nanoclusters (24.5 µg/mL) causing no toxicity in the normal human liver L02 cell line after 72 h of exposure 62,63. In contrast, production of pro-inflammatory cytokines has been demonstrated in primary rat hepatocytes after 4 h of incubation with 20 nm AuNPs (211.2 µg/mL), showing a higher sensitivity than liver macrophages 64.…”
Section: Discussionsupporting
confidence: 79%
“…This uptake did not translate into significant cytotoxicity after 24 h of exposure. The latter is consistent with 3.2 nm dihydrolipoic-coated gold nanoclusters (24.5 µg/mL) causing no toxicity in the normal human liver L02 cell line after 72 h of exposure 62,63. In contrast, production of pro-inflammatory cytokines has been demonstrated in primary rat hepatocytes after 4 h of incubation with 20 nm AuNPs (211.2 µg/mL), showing a higher sensitivity than liver macrophages 64.…”
Section: Discussionsupporting
confidence: 79%
“…The viability assay showed that the growth inhibitory rates of nanosilver to HepG2 cells were time- and dose-dependent, while L02 cell viability was not affected at a concentration of nanosilver below 80 µg mL −1 for 24 h. The result indicated that HepG2 cells are more sensitive than are L02 cells when exposed to nanosilver under the same concentration. Others 39 had similar results with HepG2 and L02 cells treated with gold nanoclusters. The toxicity of nanosilver reportedly depends largely on the release of silver ions.…”
Section: Discussionmentioning
confidence: 59%
“…To evaluate the potential application of the constructed MIP nanoparticles in DDS, the cytotoxicity tests of MIP and N-MIL on HepG2 cells and HL-7702 cells [ 41 , 42 , 43 , 44 , 45 , 46 ] were detected by MTT method ( Figure 8 ). The cell viability showed that the inhibition rate increased with time increasing.…”
Section: Resultsmentioning
confidence: 99%